2020
DOI: 10.6007/ijarbss/v10-i2/6918
|View full text |Cite
|
Sign up to set email alerts
|

The Students’ Beliefs on using Code-Switching in the ESL Classrooms

Abstract: The use of code-switching (CS) in English as Second Language (ESL) classrooms is an issue that has always been debated due to its pros and cons. This study aimed to identify the pre-university students' beliefs towards the use of CS in ESL classrooms. 91 pre-university students from a secondary school in Pasir Puteh, Kelantan participated in this study. This study employed a cross-sectional survey research design. The data were collected through the 19-item adapted questionnaire. Then, the frequency analysis v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…From the dataset, it is noticeable that the above linguistic occurrence transpired to a varying degree both oral and written forms with documented purposes and functions in ESL context. According to Razak & Shah (2020) codeswitching in ESL classrooms has positive impact used as a strategy to acquire the target language which is also one of the salient points of the current study. In fact, students code-switch for non-linguistic purposes such as establishing rapport and interpersonal relationships as well as maintaining the line of communication without disruption to circumvent any sort of conflict or misinterpretation (Hussein, et al, 2020).…”
Section: How Prevalent Is Codeswitching On Subjects With English As A...mentioning
confidence: 88%
“…From the dataset, it is noticeable that the above linguistic occurrence transpired to a varying degree both oral and written forms with documented purposes and functions in ESL context. According to Razak & Shah (2020) codeswitching in ESL classrooms has positive impact used as a strategy to acquire the target language which is also one of the salient points of the current study. In fact, students code-switch for non-linguistic purposes such as establishing rapport and interpersonal relationships as well as maintaining the line of communication without disruption to circumvent any sort of conflict or misinterpretation (Hussein, et al, 2020).…”
Section: How Prevalent Is Codeswitching On Subjects With English As A...mentioning
confidence: 88%
“…As a result, they offered suggestions for how to include some aspects of native languages in educational classroom instruction. Some literature indicated that the switching of codes improves learning and instruction in academic subjects (Hussein, Saed & Haider 2020;Kusumo Adi & Ambarini 2022;Murtiningsih et al 2022;Razak & Shah 2020). Teachers frequently establish an accepting atmosphere for communicating with learners of the English language in the senior phase even if they frequently employ code-switching to teach substantive subjects in the educational setting.…”
Section: Empirical Literaturementioning
confidence: 99%